Biogas-based electricity production from landfills in places of irregular disposal: Overview for the southeast region of Brazil - Moraes, Camile Aredes; Santos, Lucas de Lima Casseres dos; Oliveira, Augusto Cesar Laviola de; Botelho, Daniel Fioresi; Moltó Berenguer, Julia; Renato, Natalia dos Santos (Energy (Oxford), 2024)
In Brazil, a substantial part of its urban population has its waste disposed of at inappropriate places, such as open dumps and controlled tipping. This causes environmental impacts, in addition to disregarding the positive externalities arising from the correct waste disposal. Given this scenario, this research aimed to estimate the potential for generating electricity, considering the implementation of sanitary landfills to serve municipalities with inadequate waste disposal. The study had its methodology tested in municipalities in the most populous region of Brazil, the Southeast. A Python algorithm to calculate the methane production from the waste was created based on the software Landfill Gas Emission Model (LandGEM). Moreover, another algorithm was developed to allocate the mini plants based on the electricity generated, to optimize the logistics of the distance. The CO2 emission reduction due to sanitary landfills opening was predicted as well. If the sanitary landfills were to be implemented, an amount of 11,795.7 GWh would be generated over the 20 years of study and an average value of 467.1 million tons of CO2 would no longer be emitted per year. Public policies are necessary for this scenario to become a reality in Brazil, such as research incentives and market development. •Potential for energy production from sanitary landfills gases was assessed.•Python algorithm was used to calculate methane production from waste.•We developed an optimization for allocation of micro plants based on generated electricity.•There is a potential to generate 11,795.7 GWh over the 20 years of study in the region.•There is a potential to stop emitting 467.1 million tons of CO2 per year.